2020
DOI: 10.1002/joc.6531
|View full text |Cite
|
Sign up to set email alerts
|

Recently increased cold air outbreaks over Mongolia and their specific synoptic pattern

Abstract: In recent years, extreme cold air outbreak events (COEs) in winter have tended to occur more frequently over the mid‐latitudes of Eurasia, including Mongolia, despite marked warming across the continent. In the 2000s, an increase in COEs contributed to huge losses of livestock throughout Mongolia, causing socioeconomic stagnation. This study diagnosed the interdecadal variability of the frequency of COEs during cold season (November–March) using observations from 70 meteorological stations in Mongolia by contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Thus, we attempt to estimate the Mongolia data from longer records from Siberia, which can go back to 1820. Existing studies suggest the winter temperatures between Mongolia and Siberia are correlated spatially, driven by polar jet dynamics (He et al, 2017;Iijima and Hori, 2018;Munkhjargal et al, 2020). First, winter temperatures in Mongolia will be simulated by using instrumental temperature data from Siberia (in Sect.…”
Section: Simulating Annual Minimum Temperature In Mongolia Using Sibe...mentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, we attempt to estimate the Mongolia data from longer records from Siberia, which can go back to 1820. Existing studies suggest the winter temperatures between Mongolia and Siberia are correlated spatially, driven by polar jet dynamics (He et al, 2017;Iijima and Hori, 2018;Munkhjargal et al, 2020). First, winter temperatures in Mongolia will be simulated by using instrumental temperature data from Siberia (in Sect.…”
Section: Simulating Annual Minimum Temperature In Mongolia Using Sibe...mentioning
confidence: 99%
“…Furthermore, another study concluded that dzud frequency is expected to increase with future climatic changes, while using the Coupled Model Intercomparison Project's climate models (Bayasgalan et al, 2009). Natsagdorj (2001) shows that the trends of drought and the dzud index, estimated by normalized monthly temperature and precipitation, are increasing. However, these studies are based on observational data of dzud, which are available only from about 1940.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation